'Thinking' terminologies from Qurónic perspective and their impact on human intellectual development. (1st January 2011) - Badi, Jamal
The 'Qur'ān' as a divine book has terms that are used and related to 'thinking' such as TaÎawwur (conceiving), Idrak (perceiving), Fiqh (grasping), TaÑaqqul (reasoning), Tadhakkur (contemplating) etc. This paper explores major Qur'ānic terms related to thinking with the aim of uncovering potential value of these terms for human life. For this purpose, both textual and contextual analyses have been applied, as appropriate. The paper argues that internalising the Qur'ānic terms for thinking will contribute to the uplift of the global struggle on formalisation of thinking in public and private places for rightful human thought. The positive influence of Qur'ānic thinking will not remain limited to individuals, but will also affect communities through influence of human thought and behaviour which, in turn, will lead to a paradigm shift in the academic realm.